Application of 40% Trichloroacetic Acid in the Treatment for Recurrent Genital Herpes - Dawood S. Idan (Al-Anbar Medical Journal)
Background: Genital herpes is one of the common sexually transmitted diseases affect more than 400,000,000 individuals worldwide. The disease characterized by relapse and remission courses and caused by herpes simplex virus (HSV) type 2. However, satisfactory curative agents are still unavailable. Objectives: This study intends to evaluate the benefit of 40% Trichloroacetic acid (TCA) in the management of recurrent genital herpes lesions of the external male genitalia and to detect the recurrence rate during this therapeutic regimen. Materials and Methods: The study extended between 1998 to 2017 and totally, 175 patients with active disease were treated by oral administration of acyclovir 400mg 5 times per day for 5 days. Only 99 patients were followed up for one year and enrolled in the study. After 2 weeks, the recurrent cases were subjected to the chemicals peeling using topical application of 40% TCA at the site of reactivation. Results: The most affected age group was 40-50 years (n=45, 45.45%). The neck of the penis was the most affected site (n=56, 56.57%). Forty patients had only one recurrence during a one-year follow-up after treatment with 40% TCA.   Conclusion: This study approved the clinical effectiveness of the topical application of 40 % TCA in reducing the recurrence rate of the genital herpes lesions. We recommend using this chemical peeling method in the treatment of patients with genital herpes.